2021
DOI: 10.3389/fonc.2021.669746
|View full text |Cite
|
Sign up to set email alerts
|

Local Anesthetic Lidocaine and Cancer: Insight Into Tumor Progression and Recurrence

Abstract: Cancer is a leading contributor to deaths worldwide. Surgery is the primary treatment for resectable cancers. Nonetheless, it also results in inflammatory response, angiogenesis, and stimulated metastasis. Local anesthetic lidocaine can directly and indirectly effect different cancers. The direct mechanisms are inhibiting proliferation and inducing apoptosis via regulating PI3K/AKT/mTOR and caspase-dependent Bax/Bcl2 signaling pathways or repressing cytoskeleton formation. Repression invasion, migration, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 130 publications
0
14
0
1
Order By: Relevance
“…Our studies proved that anti-HBV treatment can attenuate inflammation, decreased the risk of HCC occurrence, and prevent postoperative recurrence of HCC ( 93 , 95 ). Long-term use of non-steroidal anti-inflammatory drugs can also reduce the occurrence and recurrence of cancers ( 123 126 ). Targeting cancer stemness- and/or EMT-related signaling pathways might contribute to the eradication of malignant diseases ( 127 129 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our studies proved that anti-HBV treatment can attenuate inflammation, decreased the risk of HCC occurrence, and prevent postoperative recurrence of HCC ( 93 , 95 ). Long-term use of non-steroidal anti-inflammatory drugs can also reduce the occurrence and recurrence of cancers ( 123 126 ). Targeting cancer stemness- and/or EMT-related signaling pathways might contribute to the eradication of malignant diseases ( 127 129 ).…”
Section: Discussionmentioning
confidence: 99%
“…Local anesthetics (LAs) are a group of small molecule drugs widely used in clinical anesthesia and analgesia. With the widespread involvement of LA in cancer-related surgery, there is growing clinical evidence that the use of LA during or after surgery generally improves patient outcomes [ 68 ]. Studies have shown that LAs can kill tumor cells if they come into direct contact with them [ 69 ].…”
Section: Cutaneous Melanomamentioning
confidence: 99%
“…In breast cancer surgery LIDO contributes to prevent both acute and chronic pain after breast cancer surgery ( Grigoras et al, 2012 ). And it was shown to have anticancer properties ( Chamaraux-Tran and Piegeler, 2017 ; Chamaraux-Tran et al, 2018 ; Wall and Buggy, 2021 ; Zhang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%